Pembentukan Akhlak melalui Pembacaan Juz ‘Amma - Yulianika, Yulianika; Ummi, Farkhatul (Jurnal Pendidikan Madrasah, 2024)
Indonesia's national education aims to develop the potential of students, one of which is through the cultivation of moral education. Moral education seeks to instill moral values and good character in students’ lives so that they become individuals with noble character. One effective method for shaping students' character is through the recitation of Juz ‘Amma. This study aims to explore the implementation of Juz ‘Amma recitation at SDI Nurul Hidayah as a strategy for moral education. This research uses a qualitative method with a descriptive approach. Based on the findings, the Juz ‘Amma recitation activities implemented at SDI Nurul Hidayah have proven effective in fostering students’ moral development. The routine of reciting Juz ‘Amma before lessons begin creates a religious environment and reinforces positive habits among students. Moreover, the recitation of Juz ‘Amma helps students to understand the moral values contained in the verses of the Qur’an, such as honesty, patience, and piety.